THE CORRELATION BETWEEN CONCEPT GAINING AND RETENTION IN PQ4R, TPS, AND PQ4R-TPS LEARNING STRATEGIES - Setiawati, Henny; Corebima, Aloysius Duran (Advances in Social Sciences Research Journal, 2017)
Concept gaining and retention are two important things in learning. Concept gaining is the knowledge the students gain after they follow a learning process. While retention is the ability to remember concepts within a certain period of time on the material being taught. This research aimed at exploring the correlation between concept gaining and retention of the students who learned by using  PQ4R, TPS, and PQ4R-TPS learning strategies, and comparing the regression lines related, whether they were parallel or not. The results of this research showed that there was a significant correlation between concept gaining and retention in all the three learning strategies. The highest contribution value was detected at TPS, followed by PQ4R-TPS, and PQ4R strategy. The results of further analysis reveal that the biggest slope or the rate of students’ retention in relation with the concept gaining is found at the TPS learning strategy. This fact indicates that the biggest potential of the increase of students’ retention due to concept gaining is found at the TPS learning strategy. In other words, TPS learning is the most effective learning strategy in empowering students’ concept gaining and retention compared to the two other learning strategy. Nonetheless, PQ4R and PQ4R-TPS learning strategies also have the potential to empower students' concept gaining and retention, that can be seen at the contribution of each learning strategy. This information is valuable for teachers in implementing appropriate learning strategies to improve students’ concept gaining because it is believed to have an effect on students’ retention.